An unusually productive microearthquake sequence brings new insights to the buried active thrust system of Montello (Southeastern Alps, Northern Italy) - Peruzza, Laura; Romano, Maria Adelaide; Guidarelli, Mariangela; Moratto, Luca; Garbin, Marco; Priolo, Enrico (Frontiers in Earth Science, 2022)
In August 2021, an extremely productive seismic sequence took place in northeastern Italy. Within one month, we identified and localized 407 microearthquakes in the area monitored by the local Collalto Seismic Network. This is about 20 times the average monthly rate of events detected in the last decade; 92% of them are clustered near the village of Refrontolo at about 9 km depth (main event a ML2.5, MW2.4). None of the Refrontolo sequence earthquakes were felt by the population. The earthquakes, mostly identified by automatic procedures, were post-processed by manual picking of P, S-phases and polarities; they were localized by different techniques and define a small SE dipping volume that departs from the brittle surface previously enlightened by microseisms and assigned to the NNW dipping Montello Thrust. We interpret the sequence ruptured pre-stressed patches near to failure of sub-vertical, antithetically oriented faults. The unusual productivity rate and precursory foreshock activity support the hypothesis that the Montello system has a relevant aseismic component. We believe that this episode, of no importance from an energetic point of view, is of greatest interest for deciphering the seismic potential of this area and for strengthening automatic microearthquake detection and location procedures.